Bioaugmentation of a biomixture with actinobacteria for atrazine removal - Ocante, Teresa Ana Lia (2019)
Biopurification systems (BPS) are simple and economical constructions designed to retain and degrade pesticides, in order to reduce or avoid point-source contamination. An organic biomixture (BM) constitutes the most abundant and important component of a BPS. The bioaugmentation of the BM with pesticide-degrading microorganisms is a very interesting approach to optimize its efficiency. Atrazine (ATZ) is a selective herbicide commonly applied to control the appearance of weeds in crops, mainly corn, sorghum, and sugarcane. The aim of this study were to select actinobacteria capable of removing ATZ and to evaluate the effect of the bioaugmentation of a BM with the selected actinobacteria on ATZ dissipation.A qualitative determination of tolerance to ATZ was performed by streaking 14 actinobacteria strains on Petri dishes containing starch casein agar medium with a central channel containing the ATZ solution (1000 mg L-1 and 50000 mg L-1). The tolerant strains were used to perform a quantitative determination of their ability to grow in the presence of ATZ (50 mg L-1) and to remove it from liquid minimal medium (MM). Controls were carried out in MM supplemented with glucose (1 g L-1). Microbial growth (dry weight) and residual concentration of ATZ (gas chromatography, GC) were determined after 96 h. The actinobacterium which presented the highest removal of ATZ and did not show growth inhibition in the presence of ATZ was used to inoculate a BM composed of soil, straw, and agricultural sugarcane crop residue (25:25:50). Periodic samples were collected to determine residual ATZ, total heterotrophic microorganisms (CFU g-1 BM), fluorescein diacetate hydrolysis (FDA) and acid phosphatase (AP) activities.All actinobacteria were highly tolerant to 1000 mg L-1 of ATZ and moderately tolerant to 50000 mg L-1 of ATZ. All of them were able to grow in MM supplemented with ATZ, however most of them reached statistically lower biomass than the obtained with glucose as carbon source, with the exception of Streptomyces sp. A2, A11, and M7. These strains were able to use ATZ as carbon source and to remove it from MM, presenting removal values ranging between 10% and 75%. Based on the microbial growth and ATZ removal, Streptomyces sp. M7 was selected to bioaugment the BM. The inoculation of the BM with Streptomyces sp. M7 improved significantly the ATZ removal (58%) respect to the non-biougmented BM (38%) after 28 days of incubation. The total heterotrophic population in the bioaugmented and contaminated BM (4.55 x 107 CFU g-1) did not present statistical variation respect to non-inoculated control, nor non-contaminated control. Enzymatic activities obtained in these systems ranged between 44.9 ± 0.03 and 87.2 ± 20.3 g fluorescein g-1 h-1 for FDA, and 91.82 ± 5.7 and 159.0 ± 9.0 µg p-nitrophenol g-1 h-1 for AP. These results suggest that the bioaugmentation of BM with Streptomyces sp. M7 represents a promising tool to reduce ATZ concentration in BPS.